2021
DOI: 10.1016/j.jmig.2020.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Excision versus Ablation for Management of Minimal to Mild Endometriosis: A Systematic Review and Meta-analysis

Abstract: The aim of this systematic review and meta-analysis was to perform an updated analysis of the literature in regard to the surgical management of minimal to mild endometriosis. This study evaluated women of reproductive age with superficial endometriosis to determine if the results of surgical excision compared with those of ablation in improved pain scores postoperatively. Data Sources: The following databases were searched from inception to May 2020 for relevant studies: Cochrane Central Register of Controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Surgery remains a mainstay of current treatment for endometriosis 163,169–188 . In general, surgery is indicated in symptomatic patients failing, unable to tolerate or declining medical regimens, in those attempting to conceive, and/or for infertility, and to exclude malignancy in the case of an adnexal mass 117 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery remains a mainstay of current treatment for endometriosis 163,169–188 . In general, surgery is indicated in symptomatic patients failing, unable to tolerate or declining medical regimens, in those attempting to conceive, and/or for infertility, and to exclude malignancy in the case of an adnexal mass 117 .…”
Section: Methodsmentioning
confidence: 99%
“…From this limited amount of data, no significant difference in mean visual analog scale (VAS) was seen between excision and ablation in terms of dysmenorrhea, dyspareunia, or dyschezia. 180 A 2021 systematic review and meta-analysis of two RCTs from 2001 and 2002 of patients with mild-to-moderate stage endometriosis concluded that laparoscopic excision of endometriosis is superior to ablation in all aspects of endometriosisassociated pain including dysmenorrhea, dyspareunia, dyschezia, and chronic pelvic pain. 181 The only study with longer term follow-up by Healey in 2014 reported a double-blind randomized trial of patients with nondeeply infiltrating endometriosis followed over 5 years.…”
Section: Laparoscopic Excision Versus Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Little evidence shows that surgery to treat isolated superficial peritoneal endometriosis improves overall symptoms and quality of life. The uncertainty around surgical management of this subtype is compounded by the limited evidence to allow an informed selection of specific surgical modalities to remove the lesions (for example, laparoscopic ablation versus laparoscopic excision) 139140…”
Section: Management Of Endometriosis Associated Painmentioning
confidence: 99%
“…A 2017 meta-analysis showed improved dysmenorrhea and dysmenorrhea with excision compared to ablation for all disease stages at 12 months postoperatively [22]. A 2021 meta-analysis of patients with mild to moderate endometriosis found no difference in pain outcomes for excision versus ablation [23 ▪▪ ]. Despite a lack of robust evidence, a growing body of surgeons and patients favor excision due to concerns for incomplete treatment with ablation alone.…”
Section: Surgical Treatmentmentioning
confidence: 99%